Review on mushroom mycelium-based products and their production process: from upstream to downstream - Hyun-Jae Shin; Hyeon-Su Ro; Moriyuki Kawauchi; Yoichi Honda (Bioresources and Bioprocessing)
Abstract The global trend toward carbon neutrality and sustainability calls for collaborative efforts in both the basic and applied research sectors to utilize mushroom mycelia as environmentally friendly and sustainable materials. Fungi, along with animals and plants, are one of the major eukaryotic life forms. They have long been utilized in traditional biotechnology sectors, such as food fermentation, antibiotic production, and industrial enzyme production. Some fungi have also been consumed as major food crops, such as the fruiting bodies of various mushrooms. Recently, new trends have emerged, shifting from traditional applications towards the innovative use of mushroom mycelium as eco-friendly bioresources. This approach has gained attention in the development of alternative meats, mycofabrication of biocomposites, and production of mycelial leather and fabrics. These applications aim to replace animal husbandry and recycle agricultural waste for use in construction and electrical materials. This paper reviews current research trends on industrial applications of mushroom mycelia, covering strain improvements and molecular breeding as well as mycelial products and the production processes. Key findings, practical considerations, and valorization are also discussed. Graphical Abstract